RESPON TIGA VARIETASKELAPA SAWIT (Elaeis guineensis Jacq.)DI PEMBIBITAN UTAMA TERHADAP PEMBERIAN BEBERAPA VOLUME AIR - Andri Ansyah; Fetmi Silvina; Isna Rahmadini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
ABSTRACTThis research aims to determine the response of three palm oil varieties (Elaeis guineensis Jacq.) in the main nursery on giving of several volumes of water. This research was conducted with factorial experimental methods arranged according to a CompletelyRandomized Design (CRD), this research consisted of 2 factors, namely: Factor I = Palm oil Varieties, V1: Tenera Marihat Varieties originating from PPKS, V2: Tenera Topaz 3 varieties from AA Topaz , V3: Tenera Lame variety from Socfindo, Factor II = Water supply, A1: 1000 ml per day per seed, A2: 1500 ml per day per seed, A3: 2000 ml per day per seed, A4: 2500 ml per day per seed . The research consisted of 12 treatment combinations and each treatment combination was repeated 3 replications so that 36 experimental units were obtained, each experimental unit had 3 plants to obtain 108 seeds. The results showed that: the interaction of giving several volumes of water and varieties had an effect on the humps of palm seeds, the Marihat variety showed a good response to the growth ofpalm seeds compared to the other two varieties (topaz and socfindo), giving 2500 ml per day per seed showed the good growth for all three varieties, while giving of 1000-1500 ml per day per seed of water per seed showed depressed growth in topas and socfindo varieties.Keywords: oil palm varieties, Main nursery, volumes of water